Communication and Emotional Barriers Faced by Adolescents with ADHD - Simran Choudhary; Arpit Yadav (International Journal of Indian Psychȯlogy, 2025)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition that is not much talked about. This lack of awareness can make the life of those diagnosed with ADHD more challenging. This qualitative study was conducted to determine the effects of ADHD on the communicational and emotional development of adolescents. A total of 15 participants were part of this study. The participants included adolescents between the ages of 13 to 19 years. All of the participants resided in the Delhi National Capital Region (NCR). Semi-structured interviews were used to collect data. The key findings highlighted that adolescents with ADHD find it challenging to express their emotions, and they also find it difficult to start a conversation in the first place. The adolescents take the help of simple techniques such as meditation to work on their symptoms. Most adolescents do not go for therapy or medication. They wish people were more understanding and emotionally available. There’s also a need for people to bring minor changes in their ways of communication so that they would feel comfortable in their feelings as well and not feel left out. When asked about the current state the responses were neutral although the majority of adolescents expressed stress regarding school work and lack of assistance from the education system. There are many factors that are interdependent such as emotional and communicational issues. Increased support from society and the education system can decrease the stress level in adolescents. The study highlights recommendations to improve the lives of children with Attention Deficit Hyperactivity Disorder. The study suggests that parents and surroundings of these adolescents should be more aware of these adolescents’ issues and the education system should bring provisions in all schools to help children with any mental health issues.